(untitled) (Research, Society and Development, 2022)
Arboviruses are diseases caused by arboviruses, including the Dengue virus, Zika, Chikungunya fever, and includes all those transmitted by arthropods (insects and arachnids). In this study two variables were analyzed: the incidence of Dengue, Zika and Chikungunya fever cases for the same month, and the monthly rainfall index of the municipality of Balsas Maranhão, through the website of the National Meteorological Institute. Through the graph study the average precipitation related to the cases of the three diseases in question was observed. It was observed that the amount of rainfall was an important item related to the incidence of the cases: Zika virus and Chikungunya fever had a higher frequency in the dry season while the incidence of Dengue virus was higher in the rainy season. As Balsas is outstanding because it is one of the great urban centers of the south of Maranhão, and it counts on hospital attendance of citizens of neighboring municipalities, it is important that there is the internalization of laboratories of reference for the detection of etiological agents of the vectors as well as continuous surveillance actions and epidemiological control of A. egypti.